Gender quotas or girls' networks? Towards an understanding of recruitment in the research profession in Italy - Daniele Checchi; Simona Cicognani; Nevena Kulic (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This article investigates the role of the gender composition of selection committees and networks in promoting women in research activities. We exploit a novel data set on recruitment processes at entry-level research positions in a leading Italian research centre that mainly operates in hard science. We find some evidence of discrimination against women at non-tenured entry levels, which is attenuated (or even reversed) by the presence of a woman on the selection committee. However, the most important predictor for recruitment seems to be previous connections with the research centre, which also serves as an important mechanism for women to enter the research profession. We conclude that quotas could be a solution for gender-biased preferences towards same-sex candidates in selection committees for non-tenure-track positions. Moreover, more gender-neutral networks would be another mechanism to bring more equality between men and women in research.
Keywords: J16; J71; J45; 330